A study on pregnant women's satisfaction with maternal and child healthcare service quality in Mimika, Indonesia - Maria Rante Tandung; Yenny Puspitasari; Nurwijayanti Nurwijayanti (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: One of the efforts to improve maternal and child health is through high-quality maternal and child healthcare services. High-quality maternal and child healthcare services contribute to patient satisfaction. Patient satisfaction is an emotional response that arises from the services received by comparing them with personal expectations. Pregnant women's satisfaction increases when the healthcare services provided align with their needs. Purpose: To determine pregnant women's satisfaction with maternal and child healthcare service quality in Mimika, Indonesia. Method: An analytical observational approach with a cross-sectional design to assess pregnant women’s satisfaction with maternal and child healthcare (MCH) service quality. The research was conducted in August 2024 at Kwamki Community Health Center, Mimika Regency, involving 103 respondents selected using a simple random sampling technique. The independent variable in this study was the quality of MCH services, which included tangibility, reliability, responsiveness, assurance, and empathy. The dependent variable was pregnant women's satisfaction, measured using a structured questionnaire with closed-ended questions on a Likert scale. Results: The majority of respondents were aged 26-35 years (66 respondents, 64.1%), had completed elementary school (81 respondents, 78.6%), and were housewives (94 respondents, 91.2%). Most respondents (63 respondents, 61.1%) expressed satisfaction with the services provided, as all maternal and child healthcare quality indicators were categorized as good. The satisfaction levels were associated with tangibility (54.4%), reliability (49.9%), responsiveness (66.0%), assurance (55.4%), and empathy (60.2%), with each having a p-value < 0.05. Conclusion: High-quality maternal and child healthcare services contribute to increased satisfaction among pregnant women. There is a significant relationship between the quality of healthcare services and patient satisfaction.